Prevalence and prediction of difficult intubation in Nepalese population - Shah, Shristi (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Prevalence of difficult intubation is estimated as 3 -18% during routine anesthesia. There are various bedside tests to predict the difficult intubation, like Mallampati test, Thyromental distance, Sternomental distance and mouth opening. However, the prevalence and prediction in Nepalese population is still not estimated. So this study is to see the prevalence and to compare the efficacy of airway parameters to predict the difficult intubation in Nepalese population. Methods: A prospective study was done to estimate the prevalence and prediction of difficult intubation in Nepalese population. During six months period, 182 patients who were undergoing routine surgery under General anesthesia were included in the study. Mallampati grading, thyromental distance, mouth opening and sternomental distance were recorded in preoperative assessment. Cormack and Lehane grading were done during intubation and Grade I and II are considered as easy intubation/ laryngoscopy and III and IV are considered as difficult intubation. Results: The prevalence of difficult intubation was 4.9%. Sensitivity of different tests were as follows; Mallampati test – 55%, thyromental distance – 33%, mouth opening – 22% and sternomental distance – 11%. The Specificity of the test as Mallampati test – 98%, thyromental distance – 89%, mouth opening – 96% and sternomental distance – 97%. So the Mallampati test is more sensitive and specific among the tests done. Conclusion: This prospective study shows that the prevalence of difficult intubation is not different in Nepalese population and the bedside predictors also are good tests that could be continued in our population. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 17-20